2017
DOI: 10.1371/journal.pone.0188099
|View full text |Cite
|
Sign up to set email alerts
|

Maternal aging affects oocyte resilience to carbonyl cyanide-m-chlorophenylhydrazone -induced mitochondrial dysfunction in cows

Abstract: Mitochondrial quality control is important for maintaining cellular and oocyte viability. In addition, aging affects mitochondrial quality in many cell types. In the present study, we examined how aging affects oocyte mitochondrial biogenesis and degeneration in response to induced mitochondrial dysfunction. Cumulus oocyte complexes were harvested from the ovaries of young (21-45 months) and aged (!120 months) cows and treated for 2 hours with 10 μM carbonyl cyanide-m-chlorophenylhydrazone (CCCP), or a vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…CCCP treatment has been used to enhance mitochondrial quality control in cells [ 20 ]. We showed that CCCP treatment of bovine and porcine COCs did not reduce developmental ability but enhanced mitochondrial biogenesis and degradation in oocytes [ 13 , 21 ]. From these facts, it is conceivable that short duration of CCCP treatment may reversibly affect mitochondrial conditions in oocytes and cells, and enhance mitochondrial kinetics in both cells.…”
Section: Discussionmentioning
confidence: 99%
“…CCCP treatment has been used to enhance mitochondrial quality control in cells [ 20 ]. We showed that CCCP treatment of bovine and porcine COCs did not reduce developmental ability but enhanced mitochondrial biogenesis and degradation in oocytes [ 13 , 21 ]. From these facts, it is conceivable that short duration of CCCP treatment may reversibly affect mitochondrial conditions in oocytes and cells, and enhance mitochondrial kinetics in both cells.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of porcine oocytes with resveratrol increased mitochondrial biogenesis and degradation in the oocytes, through SIRT1 activation and improved their developmental ability [ 10 ]. Moreover, CCCP-induced mitochondrial dysfunction has been found to differentially influence oocyte developmental ability and mitochondrial synthesis between young and aged cows; the differential mitochondrial response may be attributed to the differential activation of SIRT1 between the two age groups following CCCP treatment [ 11 ]. Based on these studies, it may be suggested that the up-regulation of SIRT1 expression induced by resveratrol may attenuate mitochondrial dysfunction in oocytes and embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Ageing has a well described effect on mitochondrial quantity and quality (Pantos et al 1999, Iwata et al 2011, Bartmann et al 2004. The oocyte quality decreases with maternal age and the ageassociated mitochondrial deterioration is closely related to this decline in oocyte quality (Pantos et al 1999, Tilly and Sinclair 2013, Kansaku et al 2017b. Several studies described a decrease in the mitochondrial DNA copy number, decline in the ATP content and increased levels of reactive oxygen species (ROS) in oocytes in different Vol.…”
Section: Energy Metabolism Of Granulosa Cells and Oocytesmentioning
confidence: 99%
“…Several studies described a decrease in the mitochondrial DNA copy number, decline in the ATP content and increased levels of reactive oxygen species (ROS) in oocytes in different Vol. 69 animal species (Simsek-Duran et al 2013, Rambags et al 2014, Kansaku et al 2017b. Kansaku et al (2017b) described a lower level of mitochondrial biogenesis and an inadequate activation of mitochondrial biogenesis in response to uncoupler-induced mitochondrial dysfunction in oocytes of aged cows.…”
Section: Energy Metabolism Of Granulosa Cells and Oocytesmentioning
confidence: 99%